Deskripsi Pembelajaran Sains Anak Menggunakan Media Audio Visual Kelompok B - Ahmad, Aprilia; Arifin, Irvin Novita; Sutisna , Icam (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
This study aimed to describe children's science learning in Group B at TK Harapan, Sipatana Subdistrict, Gorontalo City. This study employed a qualitative descriptive method with the subjects of 22 children aged 5-6 years. Data collection was conducted through observation, interviews, and documentation. The study results indicated that children actively participate in science learning activities. The science learning activities undertaken by the children encompass five assessment aspects: observing, comparing, grouping, measuring, and communicating. However, in the comparing aspect, children found comparing items such as numbers and letters challenging. Conversely, in communicating, children performed well in presenting their work and showcasing their drawings. Therefore, science learning for children in Group B at TK Harapan, Sipatana Subdistrict, Gorontalo City, has significantly developed.